Silicon-carbon-graphite flake hollow composite microsphere as well as preparation method and application thereof

By preparing silicon-carbon-graphite sheet hollow composite microspheres with "rigid-flexible" carbon network, the powdering and structural deterioration of silicon negative electrode materials in lithium-ion batteries due to volume changes and low electronic conductivity are solved, and the problem of powdering and structural deterioration in silicon anode materials in lithium-ion batteries is achieved. High electrochemical performance and low cost battery materials.

CN119481019AInactive Publication Date: 2025-02-18SANYA SCI & EDUCATION INNOVATION PARK WUHAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510052867.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the lithium-ion battery, silicon negative electrode material in existing lithium-ion batteries has pulverization, layered peeling and side reactions due to volume changes and low electron conductivity, resulting in structural deterioration and capacity attenuation, and the preparation cost of nano-silicon powder. High, complicated process.

Method used

Using the preparation method of silicon-carbon-graphite sheet hollow composite microspheres, by mixing photovoltaic waste silicon with graphite and sucrose, ball milling and spray-drying, a hollow structure with a "rigid-flexible" carbon network is formed, which accommodates the silicon pulping process. The volume of the swells and prevents electrolyte from erosion.

Benefits of technology

It significantly improves the electrochemical performance of the material, achieves high specific capacity, long cycle life and excellent rate performance, and at the same time reduces production costs, simplifies the preparation process, and has market-oriented promotion value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481019A_ABST
    Figure CN119481019A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon-graphite flake hollow composite microsphere as well as a preparation method and application thereof. The preparation method of the hollow composite microspheres comprises the following specific steps: S1, firstly putting photovoltaic waste silicon into a hydrochloric acid solution for ultrasonic cleaning, and then performing ultrasonic cleaning again in absolute ethyl alcohol; s2, mixing the photovoltaic waste silicon cleaned in the S1 with graphite and isopropanol, and performing ball milling and drying to obtain a silicon-graphite mixture; and S3, dispersing the silicon-graphite mixture in the S2 in a sucrose solution, performing spray drying, and performing calcination in an inert atmosphere to obtain the silicon-carbon-graphite sheet hollow composite microspheres. The silicon-carbon-graphite flake hollow composite microsphere prepared by the invention has a hollow structure of a'rigid-flexible 'carbon network, micron-sized bulk silicon is coated in a hollow spherical framework formed by interpenetrating a flexible amorphous carbon network and high-conductivity graphite flakes, and the silicon-carbon-graphite flake hollow composite microsphere has high specific capacity, long cycle life and excellent rate capability; and a new thought is provided for the design of a high-capacity negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a silicon-carbon-graphite sheet hollow composite microsphere and a preparation method and application thereof. Background Art

[0002] As energy storage devices, lithium-ion batteries have the characteristics of low cost, high energy density and power density, and long cycle life. Silicon has attracted much attention due to its high capacity (about 3700 mAh / g) and cost-effectiveness.

[0003] However, the dramatic volume change of about 400% during the lithium insertion / extraction process and its low electronic conductivity (about 10 -3 The slow reaction kinetics caused by the low S / m ratio makes it prone to severe pulverization, lamellar exfoliation, and electrolyte-related side reactions, resulting in rapid structural degradation. The degradation of silicon anodes in lithium-ion batteries involves the interaction of mechanical and chemical mechanisms, which are mainly manifested as follows: volume changes during the cycle cause stress accumulation, cracking, and pulverization, which manifest as mechanical degradation; electrolyte decomposition to form the SEI layer, which consumes active lithium ions and electrolyte erosion of the silicon anode, leading to the formation of "dead silicon", which manifests as chemical degradation. The interaction between mechanical degradation and chemical degradation further accelerates the entire degradation process. This ultimately leads to rapid erosion of the silicon anode by the SEI layer, especially after pulverization, causing particle exfoliation and ultra-fast capacity decay.

[0004] Reducing the size of silicon negative electrodes has been shown to effectively inhibit pulverization and enhance reaction kinetics by shortening the electron / ion diffusion path. Studies have shown that reducing the particle size to below 150nm can effectively avoid pulverization. Currently, nanostructure designs such as nanoparticles, nanowires and nanosheets have been studied to improve cycle stability and rate performance. For example, patent CN110697702A discloses a carbon cage silicon-graphite composite material and a preparation method thereof, but the raw material used is nano silicon powder, which is costly and the preparation process is complicated. The preparation of nano silicon powder requires vapor deposition of silane or ball milling of bulk silicon at a speed of >1000rpm, which is not suitable for practical application development; patent CN111490242A discloses a method for producing silicon-carbon materials, using a silicon aluminum alloy as the raw material, which is costly, and the use of hydrochloric acid etching causes the bonding of graphite and silicon aluminum alloy to be destroyed, resulting in a weak bond and affected cycle performance.

[0005] Therefore, although existing technologies have improved battery performance, high production costs and safety issues have hindered commercialization and limited development and application. Summary of the invention

[0006] In view of this, the present invention proposes a silicon-carbon-graphite sheet hollow composite microsphere and a preparation method and application thereof. The prepared silicon-carbon-graphite sheet hollow composite microsphere has a hollow structure of a "rigid-flexible" carbon network, which can not only accommodate the volume expansion during the silicon pulverization process, but also prevent the electrolyte from corroding silicon, thereby achieving controllable regulation of the silicon pulverization process and significantly improving the electrochemical properties of the material.

[0007] The technical solution of the present invention is achieved in this way: A method for preparing hollow silicon-carbon-graphite composite microspheres, comprising the following specific steps: S1. First, ultrasonically clean the photovoltaic waste silicon in a hydrochloric acid solution, and then ultrasonically clean it again in anhydrous ethanol; S2, mixing the photovoltaic waste silicon cleaned in S1 with graphite and isopropyl alcohol, ball milling, and drying to obtain a silicon-graphite mixture; S3, dispersing the silicon-graphite mixture of S2 in a sucrose solution, spray drying, and calcining under an inert atmosphere to obtain silicon-carbon-graphite sheet hollow composite microspheres.

[0008] Furthermore, in step S1, the concentration of the hydrochloric acid solution is 0.2-0.4wt%; the frequency of the ultrasonic cleaning is 20-30kHz, and the time is 1-2h; the frequency of the second ultrasonic cleaning is 20-30kHz, and the time is 1-2h.

[0009] Furthermore, it is characterized in that in step S2, the mass ratio of the cleaned photovoltaic waste silicon to graphite is 4-8:1; the solid-liquid ratio of the graphite to isopropanol is 1:0.5-20 g / mL.

[0010] Furthermore, in step S2, the ball milling speed is 300-400 rpm, the time is 10-14 hours, and the ball-to-material ratio is 20-80:1.

[0011] Furthermore, in step S3, the solid-liquid ratio of the silicon-graphite mixture to the sucrose solution is 0.09-0.11:1 g / mL; and the concentration of the sucrose solution is 0.11-0.13 g / mL.

[0012] Furthermore, in step S3, the spray drying temperature is 200-220° C. and the time is 5-8 h.

[0013] Furthermore, in step S3, the calcination is carried out at a heating rate of 5°C / min to 850-950°C for 1-3h.

[0014] A silicon-carbon-graphite sheet hollow composite microsphere is prepared by the preparation method.

[0015] Furthermore, the structure of the hollow composite microspheres is a "rigid-flexible" carbon network structure, specifically: micron-sized bulk silicon is coated in a hollow spherical skeleton formed by the interlacing of an amorphous carbon network and graphite sheets.

[0016] The invention discloses an application of silicon-carbon-graphite sheet hollow composite microsphere in negative electrode material of lithium ion battery.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The hollow silicon-carbon-graphite sheet composite microspheres prepared by the present invention have a hollow structure of a "rigid-flexible" carbon network, with micron-sized bulk silicon encapsulated in a hollow spherical skeleton formed by the interlacing of a flexible amorphous carbon network and a highly conductive graphite sheet, which accommodates the volume expansion during the silicon pulverization process, and the amorphous carbon that forms adaptive active material expansion differentiation by high-temperature decomposition of sucrose. The amorphous carbon matrix acts as an elastic and flexible protective barrier, which prevents the electrolyte from penetrating and corroding silicon and maintains the structural integrity of the composite material by adaptively attaching to the broken and pulverized silicon particles. The graphite flakes serve as the rigid skeleton of the hollow composite microspheres, enhancing their overall robustness, and the dual-phase carbon structure realizes controllable regulation of the silicon pulverization process, significantly improving the electrochemical performance of the material. The hollow silicon-carbon-graphite sheet composite microspheres prepared by the present invention have high specific capacity, long cycle life and excellent rate performance, providing a new idea for the design of high-capacity negative electrode materials.

[0018] 2. The silicon-carbon-graphite hollow composite microspheres of the present invention can realize the electrochemical controllable pulverization of active substances. The preparation method is simple and easy to realize on a large scale. It is environmentally friendly and economical, low cost, has market promotion value, and becomes a potential application material for high-capacity and long cycle life lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a flow chart for the preparation of Si-Gr@C hollow composite microspheres in Example 1.

[0020] Figure 2 This is the SEM image of the Si-Gr@C hollow composite microspheres of Example 1.

[0021] Figure 3 The overall HAADF-STEM image, ABF image and EDXmapping image of the Si-Gr@C hollow composite microspheres in Example 1.

[0022] Figure 4 The local HAADF-STEM image, ABF image and EDXmapping image of the Si-Gr@C hollow composite microspheres in Example 1.

[0023] Figure 5These are the HAADF-STEM and ABF images of the Si-Gr@C hollow composite microspheres in Example 1 at high resolution.

[0024] Figure 6 The ADF image and EELS mapping image of the Si-Gr@C hollow composite microspheres of Example 1, wherein (b) is the EELS spectrum of the L edge of Si and the K edge of C in the three regions marked in (a).

[0025] Figure 7 The Si@SiO in the Si-Gr@C hollow composite microspheres of Example 1 x Atomic-resolution HAADF images, including magnified images of marked areas 1 and 2 and the corresponding FFT images.

[0026] Figure 8 Models and representative internal slices of the front view, top view and right view of the Si-Gr@C hollow composite microspheres of Example 1.

[0027] Fig. 9 This is the XRD pattern of the Si-Gr@C hollow composite microspheres of Example 1.

[0028] Fig.10 This is a thermogravimetric analysis curve of the Si-Gr@C hollow composite microspheres of Example 1.

[0029] Fig.11 The battery performance diagram of the Si-Gr@C hollow composite microspheres of Example 1 as the negative electrode material of the lithium half-battery is 0.2A•g -1 Cycling performance (a), rate performance (b) and at 1 A•g -1 Cycling performance under (c).

[0030] Fig.12 The battery performance diagrams are when the Si-Gr@C hollow composite microspheres of Example 1 are used as the negative electrode material of a lithium iron phosphate full battery (LiFePO4), which are the cycle performance (a) and rate performance (b) at 0.2C.

[0031] Fig.13 The SEM images and EDX spectra of the cross-section of the Si-Gr@C hollow composite microspheres of Example 1 before and after the cycle, where (a) is before the cycle and (b) is after 20 cycles.

[0032] Fig.14 The top view SEM images of the Si-Gr@C hollow composite microspheres of Example 1 before and after cycling, where (a) is before cycling and (b) is after 20 cycles.

[0033] Fig.15The in-situ XRD pattern (a) and in-situ Raman spectrum (b) of the Si-Gr@C hollow composite microspheres of Example 1.

[0034] Fig.16 These are SEM images of the Si-Gr@C hollow composite microspheres of Example 1 before and after cycling, which are before cycling, 1 cycle, 3 cycles, and 10 cycles, respectively.

[0035] Fig.17 Statistical distribution diagram of silicon particle size of Si-Gr@C hollow composite microspheres before and after cycles in Example 1, which are before cycle, 1 cycle, 3 cycles and 10 cycles respectively.

[0036] Fig.18 The HAADF-STEM image and EDXmapping image of the Si-Gr@C hollow composite microspheres in Example 1 after 10 cycles.

[0037] Fig.19 The ToF-SIMS statistics of several fragments of the Si-Gr@C hollow composite microspheres in Example 1 after 10 cycles are a three-dimensional graph (a), a graph showing the number of fragments versus etching depth (b), and a schematic diagram of SEI distribution after cycling (c).

[0038] Fig. 20 High-resolution HAADF-STEM and ABF images of the Si-Gr@C hollow composite microspheres in Example 1 after 10 cycles.

[0039] Fig.21 The model and representative internal slices of the front view, top view and right view of the Si-Gr@C hollow composite microspheres in Example 1 after 10 cycles.

[0040] Fig. 22 The BET diagram and pore size distribution diagram of the Si-Gr@C hollow composite microspheres in Example 1 before and after 10 cycles.

[0041] Fig.23 The volume, fragments and positive images of amorphous carbon extracted from the reconstructed model of Si-Gr@C hollow composite microspheres in Example 1 before and after 10 cycles.

[0042] Fig.24 The BET surface area change of the Si-Gr@C hollow composite microspheres in Example 1 before and after 10 cycles and the area change of the interface within the amorphous carbon volume are shown in FIG.

[0043] Fig.25 The battery performance diagrams of Si-Gr@C of Example 1, Si-Gr of Comparative Example 1 and Si@C of Comparative Example 2 as negative electrode materials of lithium half-cells are 0.2A•g -1Cycling performance (a) and rate performance (b) under . DETAILED DESCRIPTION

[0044] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the embodiments of the present invention, and these improvements and modifications are also considered to be within the protection scope of the embodiments of the present invention.

[0045] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0046] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0047] Example 1 A method for preparing hollow silicon-carbon-graphite composite microspheres, comprising the following specific steps: S1. Place the photovoltaic waste silicon in a 0.3wt% hydrochloric acid solution and ultrasonically clean it at 25kHz for 1h, then place it in anhydrous ethanol and ultrasonically clean it at 25kHz for 1h; S2, 80g of the photovoltaic waste silicon washed by S1, 20g of graphite and 10mL of isopropanol were mixed, ball milled at a ball-to-material ratio of 20:1 and 400rpm for 12h, and dried to obtain a silicon-graphite mixture; S3. According to the solid-liquid ratio of 0.1:1 g / mL, the silicon-graphite mixture of S2 was dispersed in a sucrose solution with a concentration of 0.12 g / mL, spray-dried at 220°C for 5 h, and calcined under an inert atmosphere, specifically: the temperature was increased to 900°C at a heating rate of 5°C / min and calcined for 2 h to obtain silicon-carbon-graphite sheet hollow composite microspheres, named Si-Gr@C.

[0048] The silicon-carbon-graphite hollow composite microspheres Si-Gr@C prepared in Example 1 were characterized in series, and the battery performance of the silicon-carbon-graphite hollow composite microspheres Si-Gr@C prepared in Example 1 was tested and the cycle performance of Si-Gr@C was measured. The specific data results are as follows: Figure 2-24 shown.

[0049] Figure 2 The SEM image of Si-Gr@C hollow composite microspheres. Figure 2 It can be seen that the material prepared in Example 1 presents a unique hollow spherical structure with a diameter of 3-8 μm.

[0050] Figure 3 , 4The overall and local HAADF-STEM images, ABF images and EDXmapping images of Si-Gr@C hollow composite microspheres are shown respectively. Figure 3 and Figure 4 It can be seen that inside the composite microsphere prepared in Example 1, silicon blocks, graphite flakes and amorphous carbon are evenly distributed, and amorphous carbon and graphite flakes are interspersed and wrapped in bulk silicon. Among them, the silicon block size is about 500nm, and it is wrapped by a thin layer of carbon layer, which can effectively prevent the volume expansion and pulverization of silicon during the charging and discharging process. The graphite flakes are interspersed between the silicon particles wrapped by the carbon layer, which can enhance the conductivity and structural strength of the material.

[0051] Figure 5 The HAADF-STEM and ABF images of Si-Gr@C hollow composite microspheres at high resolution are shown in Figure 2. Figure 5 It can be seen that amorphous carbon acts like "glue", binding silicon and graphite tightly together and forming a continuous network structure.

[0052] Figure 6 ADF image and EELS mapping image of Si-Gr@C hollow composite microspheres. Figure 7 Si@SiO in Si-Gr@C hollow composite microspheres x Atomic resolution HAADF images, from Figure 6 It can be seen that the energy loss indicates that the surface of the silicon block is oxidized to a certain extent, and the outer layer is wrapped by amorphous carbon to form Si-SiO x -C three-layer structure; Figure 7 The atomic image shows that SiO x The oxide layer is 8-10nm thick and is amorphous.

[0053] Figure 8 The three-dimensional reconstruction, three views and slices further prove that amorphous carbon and graphene sheets are interspersed and wrapped in bulk silicon.

[0054] Fig. 9 The XRD patterns show that crystalline silicon, graphite and amorphous carbon are on the Si-Gr@C hollow composite microspheres.

[0055] Fig.10 The thermogravimetric analysis curve shows that the content of carbon matrix in Si-Gr@C hollow composite microspheres is 15.4%.

[0056] Fig.11 When the Si-Gr@C hollow composite microspheres of Example 1 are used as the negative electrode material of the lithium-ion battery, when the current density is 0.2A•g -1 The specific capacity of the second cycle is 1722 mAh g -1After 100 cycles, the battery still maintained 94.2% of its capacity and exhibited excellent rate performance at a current density of 5A•g -1 The specific capacity can reach 1034 mAh g -1 When the current density returns to 0.2A•g -1 The specific capacity of the battery hardly decays. When the current density is 1A•g -1 The specific capacity of the second cycle is 1511 mAh g -1 , and still maintains 90.6% of its capacity after 200 cycles.

[0057] Fig.12 When the Si-Gr@C hollow composite microspheres of Example 1 are used as the negative electrode material of a lithium iron phosphate full battery (LiFePO4), the reversible specific capacity at 0.2C reaches 139 mAh•g -1 , and there is almost no capacity decay after 50 cycles, showing excellent cycle stability and good rate performance.

[0058] Fig.13 and Fig.14 It can be seen that during the cycle, the Si-Gr@C hollow composite microspheres exhibited excellent structural stability, with a volume expansion rate of only 13.5% and no obvious cracks.

[0059] Fig.15 The in-situ XRD and Raman spectra show that silicon is completely amorphized in the first cycle.

[0060] Fig.16 The SEM images before and after the cycle show that the overall spherical structure is maintained, but the silicon blocks in the Si-Gr@C hollow composite microspheres are pulverized during the cycle. Fig.17 The silicon particle size distribution diagram shows that nano-sized silicon particles are formed during the cycling process.

[0061] Fig.18 HAADF-STEM and EDX showed that the pulverized silicon particles were wrapped by the carbon matrix, and the SEI was mainly formed on the carbon surface with very little direct contact with silicon. Fig.19 The ToF-SIMS analysis shows the distribution characteristics of SEI on the surface of i-Gr@C hollow composite microspheres, indicating that SEI is mainly distributed in the outer carbon layer and rarely directly contacts silicon, which effectively prevents SEI from penetrating into silicon, further demonstrating the electrolyte isolation effect of the carbon matrix. Fig. 20 Local high-resolution HAADF-STEM and EDX analysis showed that although the silicon particles became smaller in size after pulverization, they were still wrapped by the carbon matrix. Fig.21The 3D tomographic reconstruction further showed that the carbon matrix can continue to wrap the pulverized silicon particles after cycling, and the graphite flakes are interspersed throughout the structure, playing a role in enhancing the structural strength.

[0062] Fig. 22 The N2 adsorption-desorption isotherm analysis of the Si-Gr@C hollow composite microspheres before and after cycling shows that the specific surface area is significantly reduced after cycling, indicating that the pulverization process of silicon mainly occurs within the limitation of the carbon matrix, and the carbon matrix can effectively accommodate the volume expansion of silicon and maintain the integrity of the material structure.

[0063] Fig.23 It can be seen that the three-dimensional reconstructed amorphous carbon matrix before and after 10 cycles is extracted through volume segmentation, and the amorphous carbon matrix still maintains a continuous and interconnected structure.

[0064] Fig.24 It can be seen that after the cycle, the interface area of ​​amorphous carbon increases and the specific surface area decreases, indicating that when the bulk silicon is crushed, the amorphous carbon adaptively and tightly wraps the powdered silicon particles, preventing the silicon particles from falling off and the erosion of the electrolyte, ensuring that the Si-Gr@C hollow composite microspheres always maintain good structural integrity during the cycle and achieve excellent cycle stability.

[0065] Comparative Example 1 The difference from Example 1 is that the sucrose solution is missing, that is, the silicon-carbon composite microspheres Si-Gr are finally prepared, and the rest are consistent with Example 1.

[0066] That is, the preparation method of the Si-Gr composite microspheres of this comparative example comprises the following specific steps: S1. Place the photovoltaic waste silicon in a 0.3wt% hydrochloric acid solution and ultrasonically clean it at 25kHz for 1h, then place it in anhydrous ethanol and ultrasonically clean it at 25kHz for 1h; S2, 80g of the photovoltaic waste silicon washed by S1, 20g of graphite and 10mL of isopropanol were mixed, ball milled at a ball-to-material ratio of 20:1 and 400rpm for 12h, and dried to obtain a silicon-graphite mixture; S3. The silicon-graphite mixture of S2 was dispersed in deionized water at a solid-liquid ratio of 0.1:1 g / mL and spray-dried at 220°C for 5 h to obtain Si-Gr composite microspheres.

[0067] Comparative Example 2 The difference from Example 1 is that graphite is missing, that is, silicon-amorphous carbon composite microspheres Si@C are finally prepared, and the rest are consistent with Example 1.

[0068] That is, the preparation method of the Si@C composite microspheres of this comparative example comprises the following specific steps: S1. Place the photovoltaic waste silicon in a 0.3wt% hydrochloric acid solution and ultrasonically clean it at 25kHz for 1h, then place it in anhydrous ethanol and ultrasonically clean it at 25kHz for 1h; S2, 80 g of photovoltaic waste silicon washed with S1 and 10 mL of isopropanol were mixed, and the mixture was ball-milled at 400 rpm for 12 h at a ball-to-material ratio of 20:1, and dried to obtain a material; S3. According to the solid-liquid ratio of 0.1:1 g / mL, the material of S2 was dispersed in a sucrose solution with a concentration of 0.12 g / mL, spray-dried at 220°C for 5 h, and calcined under an inert atmosphere, specifically: the temperature was increased to 900°C at a heating rate of 5°C / min and calcined for 2 h to obtain silicon-amorphous carbon composite microspheres, named Si@C.

[0069] The electrochemical performance of the composite microspheres prepared in Example 1 and Comparative Example 1 and Comparative Example 2 was tested. Fig.25 shown.

[0070] from Fig.25 It can be seen that when the current density is 0.2A•g -1 When the Si-Gr@C of Example 1 of the present invention has a specific capacity of 2102 mAh·g -1 After 100 cycles, the capacity is still 94.2%, while the specific capacity of Si-Gr in comparative example 1 is 2642 mAh•g -1 After 30 cycles, the capacity retention rate was only 10%, indicating that the lack of sucrose and the absence of amorphous carbon coating were not conducive to the stability of the sample; the specific capacity of Si@C in comparative example 2 for the first discharge was 2142 mAh•g -1 After 100 cycles, the capacity retention rate is 54.2%, indicating that the presence of graphite is beneficial to the stability of the sample and increases the cycle performance.

[0071] At the same time, the Si-Gr@C of Example 1 of the present invention also exhibits excellent rate performance. -1 The specific capacity can reach 1034 mAh g -1 When the current density returns to 0.2A•g -1 The specific capacity of the comparative example 1 is almost not decayed at a current density of 1A•g -1 The specific capacity is reduced to 159 mAh g -1 When the current density returns to 0.2A•g -1 The specific capacity of Si@C in Comparative Example 2 decreased significantly at a current density of 5A•g -1 The specific capacity is reduced to 453 mAh g -1 When the current density returns to 0.2A•g -1The specific capacity decayed slightly.

[0072] Comparative Example 3 The difference from Example 1 is that the ratio of photovoltaic waste silicon, graphite and sucrose is different, and the rest is consistent with Example 1.

[0073] That is, the preparation method of the silicon-carbon-graphite sheet hollow composite microspheres of this comparative example comprises the following specific steps: S1. Place the photovoltaic waste silicon in a 0.3wt% hydrochloric acid solution and ultrasonically clean it at 25kHz for 1h, then place it in anhydrous ethanol and ultrasonically clean it at 25kHz for 1h; S2, 70g of photovoltaic waste silicon washed by S1, 30g of graphite and 10mL of isopropanol were mixed, ball milled at a ball-to-material ratio of 20:1 and 400rpm for 12h, and dried to obtain a silicon-graphite mixture; S3. According to the solid-liquid ratio of 0.2:1 g / mL, the silicon-graphite mixture of S2 was dispersed in a sucrose solution with a concentration of 0.10 g / mL, spray-dried at 220°C for 5 h, and calcined under an inert atmosphere, specifically: the temperature was increased to 900°C at a heating rate of 5°C / min and calcined for 2 h to obtain silicon-carbon-graphite sheet hollow composite microspheres, named Si-Gr@C.

[0074] Comparative Example 4 The difference from Example 1 is that the rotation speed of the ball mill is different and the temperature of the spray drying is different. The rest is the same as Example 1.

[0075] That is, the preparation method of the silicon-carbon-graphite sheet hollow composite microspheres of this comparative example comprises the following specific steps: S1. Place the photovoltaic waste silicon in a 0.3wt% hydrochloric acid solution and ultrasonically clean it at 25kHz for 1h, then place it in anhydrous ethanol and ultrasonically clean it at 25kHz for 1h; S2, 80g of photovoltaic waste silicon washed by S1, 20g of graphite and 10mL of isopropanol were mixed, ball milled at a ball-to-material ratio of 20:1 and 250rpm for 12h, and dried to obtain a silicon-graphite mixture; S3. According to the solid-liquid ratio of 0.1:1 g / mL, the silicon-graphite mixture of S2 was dispersed in a sucrose solution with a concentration of 0.12 g / mL, spray-dried at 180°C for 5 h, and calcined under an inert atmosphere, specifically: the temperature was increased to 900°C at a heating rate of 5°C / min and calcined for 2 h to obtain silicon-carbon-graphite sheet hollow composite microspheres, named Si-Gr@C.

[0076] The electrochemical performance of the composite microspheres prepared in Example 1 and Comparative Examples 3 and 4 was tested, and the results are shown in Table 1.

[0077] Table 1

[0078] As can be seen from Table 1, the cycle stability of Comparative Example 3, which changes the ratio of photovoltaic waste silicon, graphite and sucrose, and Comparative Example 4, which changes the parameters of the preparation process, is reduced.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing hollow silicon-carbon-graphite composite microspheres, characterized in that: The specific steps include: S1. First, ultrasonically clean the photovoltaic waste silicon in a hydrochloric acid solution, and then ultrasonically clean it again in anhydrous ethanol; S2, mixing the photovoltaic waste silicon cleaned in S1 with graphite and isopropyl alcohol, ball milling, and drying to obtain a silicon-graphite mixture; S3, dispersing the silicon-graphite mixture of S2 in a sucrose solution, spray drying, and calcining under an inert atmosphere to obtain silicon-carbon-graphite sheet hollow composite microspheres.

2. The method for preparing hollow silicon-carbon-graphite composite microspheres according to claim 1, characterized in that: In step S1, the concentration of the hydrochloric acid solution is 0.2-0.4wt%; the frequency of the ultrasonic cleaning is 20-30kHz, and the time is 1-2h; the frequency of the second ultrasonic cleaning is 20-30kHz, and the time is 1-2h.

3. The method for preparing hollow silicon-carbon-graphite composite microspheres according to claim 1, characterized in that: In step S2, the mass ratio of the cleaned photovoltaic waste silicon to graphite is 4-8:1; the solid-liquid ratio of the graphite to isopropanol is 1:0.5-20 g / mL.

4. The method for preparing hollow silicon-carbon-graphite composite microspheres according to claim 1, characterized in that: In step S2, the ball milling speed is 300-400 rpm, the time is 10-14 hours, and the ball-to-material ratio is 20-80:

1.

5. The method for preparing hollow silicon-carbon-graphite composite microspheres according to claim 1, characterized in that: In step S3, the solid-liquid ratio of the silicon-graphite mixture to the sucrose solution is 0.09-0.11:1 g / mL; and the concentration of the sucrose solution is 0.11-0.13 g / mL.

6. The method for preparing hollow silicon-carbon-graphite composite microspheres according to claim 1, characterized in that: In step S3, the spray drying temperature is 200-220°C and the time is 5-8h.

7. The method for preparing hollow silicon-carbon-graphite composite microspheres according to claim 1, characterized in that: In step S3, the calcination is carried out at a heating rate of 5°C / min to 850-950°C for 1-3h.

8. A silicon-carbon-graphite sheet hollow composite microsphere, prepared by the preparation method according to any one of claims 1 to 7.

9. The silicon-carbon-graphite sheet hollow composite microsphere according to claim 8, characterized in that: The structure of the hollow composite microspheres is a "rigid-flexible" carbon network structure, specifically: micron-sized bulk silicon is coated in a hollow spherical skeleton formed by the interlacing of an amorphous carbon network and graphite sheets.

10. Use of the silicon-carbon-graphite sheet hollow composite microspheres as claimed in claim 8 in negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Carbon cage silicon-graphite composite material and preparation method thereof

    CN110697702A

  • Hollow silicon-carbon composite material for lithium-ion batteries, and preparation method thereof

    CN107799728A

  • Method for preparing silicon-carbon negative electrode material from photovoltaic waste silicon powder and graphene oxide

    CN114975962A

  • Preparation method for three-dimensional graphene based in-situ grown silicon negative electrode material for lithium battery, negative electrode material, and use thereof

    WO2024255390A1